Electronic Medical Records (ELMR) and the Public Perspective on Privacy Rights - Ida Wulandari; Arief Budiono; Siti Soekiswati (Dinasti Research, 2025)
This study aims to analyze the implementation of Electronic Medical Records (EMR) at Hidayah General Hospital Boyolali, focusing on the public perspective regarding patient privacy rights. The research employs a descriptive quantitative method with a survey approach. Data were collected through questionnaires filled out by 100 inpatients. The findings indicate that both the public perspective and patient privacy rights have a significant impact on the implementation of EMR. The public perspective contributes 39.4%, while patient privacy rights contribute 41.0%. Additionally, this study found that the level of EMR implementation is directly influenced by the public perspective (19.9%) and patient privacy rights (23.0%), as well as indirectly through electronic medical records (15.5% and 16.1%). These findings suggest that respecting patient privacy rights and understanding the public perspective are key factors in the successful implementation of EMR. The study recommends enhanced training for healthcare professionals, strengthening privacy policies, and developing feedback systems to improve healthcare service quality.